Broken lumbar pedicle screw - Ashish Kumar Dwivedi; Rashim Kataria; Virendra Deo Sinha (Romanian Neurosurgery, 2017)
Spinal fixation is one of the common surgical procedure performed by spine surgeons. Among the various spinal fixation technique, pedicle screw fixation is of paramount importance especially when instability is in dorsolumbar and sacral region of spine. Like any surgical procedure, pedicle screw fixation is not devoid of complications. Broken pedicle screws are one of the rare complication of this procedure with a great challenge to deal with such situation. We are reporting one of the rare complication of pedicle screw fixation with literature review and our philosophy to deal such complication.